Analysis Of The Culinary Tourism Development Strategy In Tahu Village, Islamic Economic Review - Shintiya Fadila; Tri Inda Fadhila Rahma; Nursantri Yanti (Universitas Trunodjoyo Madura, 2025)
Kampung Tahu, as a culinary tourism destination, has great potential for optimal development. To ensure its consistency with Islamic economic principles, which emphasize justice, sustainability, and shared prosperity, the implemented development plan must be examined. Therefore, this study aims to determine the strategy for developing Kampung Tahu culinary tourism from an Islamic economic perspective. This study used the Systematic Literature Review (SLR) method with a search strategy in Google Scholar and Sinta published from 2020 to 2024. The results obtained indicate that the strategy is consistent with current theory and the promotional strategy is the most strategic approach. Entrepreneurs have also applied Islamic principles in running their businesses, which include the importance of conducting business fairly, honestly, and trustworthy, as well as paying attention to the quality of raw materials that are guaranteed halal.Keywords: Development Strategy, Tourism, Culinary Tourism, Islamic Economics